1983
DOI: 10.1530/jrf.0.0680033
|View full text |Cite
|
Sign up to set email alerts
|

Pre-partum changes in the plasma concentrations of progesterone, relaxin, prostaglandin F-2  and 13,14-dihydro-15-keto prostaglandin F-2  in meclofenamic acid-treated sows

Abstract: Summary. The pre-partum plasma concentrations of progesterone, relaxin, PGF\x=req-\ 2\g=a\and 13,14-dihydro-15-keto PGF-2\g=a\(PGFM) were determined in 6 sows treated with meclofenamic acid (5\m=.\0mg/kg body wt daily, from Day 109 to Day 113 of pregnancy), and 2 sows which farrowed prematurely. The inhibition of PG synthesis with meclofenamic acid did not prevent either the decline in plasma progesterone or the release of relaxin. Three distinct stages in the progressive changes of the above hormones were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The nature of the signal initiating the release of relaxin is unlikely to come from the uterus, since the timing of the surge of relaxin was identical in both hysterectomized sows and sows in late pregnancy (Anderson, Adair, Stromer & McDonald, 1983). These data, together with the findings of Gooneratne, Bryant-Greenwood, Maule-Walker et al (1983) and Randall, Taverne, Challis et al (1986), question the role of uterine PGF2a as the natural and initial luteolytic agent (First & Bosc, 1979). It has therefore been suggested that small amounts of intra-luteal PG (Rothchild, 1981;Patek & Watson, 1983) may be responsible for the regression of the corpus luteum and thus may not be detected in the peripheral circulation by conventional radioimmunoassay.…”
Section: Discussionmentioning
confidence: 98%
“…The nature of the signal initiating the release of relaxin is unlikely to come from the uterus, since the timing of the surge of relaxin was identical in both hysterectomized sows and sows in late pregnancy (Anderson, Adair, Stromer & McDonald, 1983). These data, together with the findings of Gooneratne, Bryant-Greenwood, Maule-Walker et al (1983) and Randall, Taverne, Challis et al (1986), question the role of uterine PGF2a as the natural and initial luteolytic agent (First & Bosc, 1979). It has therefore been suggested that small amounts of intra-luteal PG (Rothchild, 1981;Patek & Watson, 1983) may be responsible for the regression of the corpus luteum and thus may not be detected in the peripheral circulation by conventional radioimmunoassay.…”
Section: Discussionmentioning
confidence: 98%
“…Results from the present study indicate no association between plasma estradiol and birth intervals and therefore do not support a role for loss of placental estrogen as a mechanism for the prolonged last birth interval. Large amounts of prostaglandin F 2␣ are released from the uterus during and after parturition (Gooneratne et al, 1983;Watts et al, 1988;Lundin-Schiller et al, 1996). Both the endometrium and placenta are likely to be sources of prostaglandin.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the effect on stillbirth is unclear but may be due to the conversion of essential fatty acids to prostaglandins, leukotrienes, and thromboxanes (Kremmyda et al, 2011). Prostaglandins affect farrowing onset and uterine contractility (First and Bosc, 1979;Gooneratne et al, 1983). Leukotrienes affect lung function, particularly in response to disease (McCarthy and Weinberg, 2012).…”
Section: Gromega + Zincmentioning
confidence: 99%